Family Role on the Pregnant Women’s Knowledge Toward Obstetric Danger Signs - Handayani, Rr. Novita Wahyu; Nasution, Ali Napiah; Lister, Clarissa (Journal of Maternal and Child Health, 2025)
Background: Obstetric danger signs are an important indicator that pregnant women need to recognize to prevent complications and reduce maternal mortality. This study aims to analyze the determinants of knowledge about obstetric danger signs in pregnant women, with a special focus on the role of family function as measured by the family APGAR instrument. Subjects and Method: A cross-sectional study was conducted on 48 pregnant women who visited the Padang Bulan Community Health Center, Medan, during August-September 2024. The dependent variable is the level of knowledge about obstetric danger signs. Independent variables were age, education level, employment status, number of pregnancies (parity), income, and family function (APGAR score). Data collection was conducted using questionnaires on obstetric danger signs and family APGAR instruments. Data analysis included univariate, bivariate (Chi-Square), and multivariate (logistic regression) analysis. Results: The majority of subjects (72.9%) had good knowledge of obstetric danger signs. Bivariate analysis showed that education level (p=0.008) and family function (p=0.005) had a significant relationship with knowledge level, while age, employment status, parity, and income showed no significant relationship. Multivariate analysis confirmed that highly functional family function (OR= 10.47; 95% CI= 1.56 to 70.40; p =0.016) and higher education levels (OR= 6.83; 95% CI= 1.31 to 35.61; p = 0.023) were significant independent predictors for good knowledge of obstetric danger signs. Conclusion: Family function and education level are the main determinants of pregnant women's knowledge about obstetric danger signs. Maternal health education programs need to consider family involvement and pay special attention to pregnant women with low levels of education to improve understanding of obstetric danger signs, which can ultimately contribute to a decrease in maternal morbidity and mortality rates.